Liminality space in-between: a feminist evaluation of primordial and modern polarities of the woman's journey in the Nigerian novel - Alkali, Muhammad; Talif, Rosli; Wan Yahya, Wan Roselezam; Mohd Jan, Jariah (Penerbit Universiti Kebangsaan Malaysia, 2014)
The option offered by the modern polarity feminist is not with the intent of sounding like magic, but it largely guarantees the disheartened opposite sex to get pretty impressive results with minimal intervention, resulting in relationship satisfaction, intimacy, love, passion, commitment, and trust. In fact, it can boast of decline in marital dissatisfaction as entirely eliminated, although there could be exceptions. This nego-feminist framework is heard throughout the paper interrogating primordialism on womanhood in Nigerian novels into those with opposition motifs to modern streaks which guarantee lively-partnership. The evaluation shows that women generally can reap maximally from the nego-feminist frame.